Peningkatan Keterampilan Membaca Puisi Siswa Melalui Model Pembelajaran Quantum Teaching Pada Siswa Di Kelas Tinggi Sekolah Dasar - Eka Sakti Ismulya; Arsyi Rizqia Amalia; Luthfi Hamdani Maula (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to describe the improvement of poetry reading skills through the Quantum Teaching learning model for students in high school elementary school and the application of the Quantum Teaching learning model to improve poetry reading skills in students in high school elementary school. The research method used was Classroom Action Research (CAR) with a research design using the Kemmis and Mc Taggart models which were carried out in two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. Participants in this study were fourth grade students of SDN 1 Cikembar as many as 36 students, consisting of 15 male students and 21 female students. Data collection techniques in this study used a test technique in the form of pre-cycle, cycle I, and cycle II. While the non-test technique is in the form of observation, field notes and documentation. The results of the pre-cycle study through the poetry reading skills indicator test showed completeness by 22%. Then increasing in the first cycle reached completeness of 64%. Whereas in the second cycle, the results of the tests showed completeness reached 84%. The overall increase with the calculation of the N-Gain formula scores 0.7 with the medium category. This Classroom Action Research (CAR) concludes that poetry reading skills are improved through the Quantum Teaching learning model for students in high school elementary school 2018/2019.